Palaeoceanography of the Barents Sea continental margin, north of Nordaustlandet, Svalbard, during the last 74 ka. (17th July 2015) - Chauhan, Teena; Rasmussen, Tine L.; Noormets, Riko
Abstract : We investigated gravity core HH11‐09GC from 488 m water depth at the northern Svalbard margin in order to reconstruct changes in Atlantic Water (AW) inflow to the Arctic Ocean. The study was based on the distribution patterns of benthic and planktic foraminifera, benthic and planktic oxygen and carbon isotopes, lithology and physical properties of the sediments. The core contains sediments from Marine Isotope Stages (MISs) 5a to 1. MIS 4 was characterized by glacial conditions and at c . 65 ka the Svalbard‐Barents Sea Ice Sheet (SBIS) advanced. Polynya was formed in front of the SBIS at c . 62 ka. During late MIS 3 (32–29 ka) and MIS 2 (22–20 ka), a strong influence of AW resulted in high productivity of both planktic and benthic foraminiferal faunas. During 23–22 ka, the SBIS advanced to the shelf edge. The last deglaciation began at 18.5 ka and at 16.9 ka 'a peak' influx of meltwater from the retreating SBIS caused a weakening of the ocean circulation. At the start of the Bølling‐Allerød interstadial at c . 15.5 ka, inflow of relatively warm AW probably intensified the release of meltwater at 14 and 12.8 ka. This probably led to expansion of sea ice cover during the Younger Dryas stadial. The late Holocene from 3.7 ka was characterized by the presence of seasonal to perennial sea ice cover and a slight warming of the bottom waters. The sea ice cover decreased for a short period at 1.5 ka owing to the advection of relatively warm AW. Correlation with results from the northwestern Svalbard margin shows that the patterns of ice retreat and advance correlate closely with changes in inflow of AW and were regulated by meltwater discharge, sea ice export and insolation.